What works in falls prevention in Asia: a systematic review and meta-analysis of randomized controlled trials - Hill, Keith D.; Suttanon, Plaiwan; Lin, Sang-I; Tsang, William W.N.; Ashari, Asmidawati; Abd Hamid, Tengku Aizan; Farrier, Kaela; Burton, Elissa (BioMed Central, 2018)
Background There is strong research evidence for falls prevention among older people in the community setting, although most is from Western countries. Differences between countries (eg sunlight exposure, diet, environment, exercise preferences) may influence the success of implementing falls prevention approaches in Asian countries that have been shown to be effective elsewhere in the world. The aim of this review is to evaluate the scope and effectiveness of falls prevention randomized controlled trials (RCTs) from the Asian region.